Ly α emission from galaxies in the Epoch of Reionization. Issue 2 (5th April 2019) - Behrens, C; Pallottini, A; Ferrara, A; Gallerani, S; Vallini, L
ABSTRACT: The intrinsic strength of the Ly α line in young, star-forming systems makes it a special tool for studying high-redshift galaxies. However, interpreting observations remains challenging due to the complex radiative transfer involved. Here, we combine state-of-the-art hydrodynamical simulations of 'Althæa', a prototypical Lyman Break Galaxy (LBG; stellar mass $M_{\star }\simeq 10^{10}\, {\rm M}_{\odot }$ ) at z = 7.2, with detailed radiative transfer computations of dust/continuum, [C ii] 158 $μ$ m, and Ly α to clarify the relation between the galaxy properties and its Ly α emission. Althæa exhibits low ( f α < 1 per cent) Ly α escape fractions and equivalent widths, EW ≲ 6 Å for the simulated lines of sight, with a large scatter. The correlation between escape fraction and inclination is weak, as a result of the rather chaotic structure of high-redshift galaxies. Low f α values persist even if we artificially remove neutral gas around star-forming regions to mimic the presence of H ii regions. The high attenuation is primarily caused by dust clumps co-located with young stellar clusters. We can turn Althæa into a Lyman Alpha Emitter (LAE) only if we artificially remove dust from the clumps, yielding EWs up to 22 Å. Our study suggests that the LBG-LAE duty-cycle required by recent clustering measurements poses the challenging problem of a dynamically changing dust attenuation. Finally, we find an anticorrelation between the magnitude of Ly α–[C ii] line velocity shift and Ly α luminosity.